The Cultural Role of Rice Cultivation in Female Workforce Participation in India - Gautam Hazarika (Institute of Labor Economics (IZA), 2024)
Rice and wheat are India's staple cereal crops and there is significant regional variation in the suitability to the cultivation of each. Both are so-called 'plough-positive' crops, whose cultivation is benefited by ploughing. It has previously been argued that the ancient adoption of the plough, a heavy implement better suited to handling by men, was a factor in the evolution of cultural norms prescribing a domestic role for women in society (Boserup, 1970). This study contends that rice is an anomalous plough-positive crop in that its cultivation, highly labor-intensive, has traditionally required much female labor. This, it is argued, may have led to a local loosening of plough culture's strictures against work by Indian women proportional to the local relative, to wheat, suitability to rice cultivation. To distinguish between a cultural effect and the technical effect of the labor-intensivity of rice cultivation, this study considers the workforce participation of urban women, spatially removed from agricultural operations. It is found that the district urban female workforce participation rates in both the 2001 and 2011 Censuses of India significantly increase in the district relative suitability to rice cultivation. Further, the increase in the district urban female workforce participation rate between 2001 and 2011 was significantly more pronounced in districts potentially better suited to growing rice than wheat. In addition, analysis of microdata from the 1999-2000 National Sample Survey of Employment and Unemployment reveals that the urban female propensity to work significantly increases in the district relative suitability to rice cultivation, though, tellingly, only so in the case of natives of the district, those whose culture will have been shaped by the local agro- ecology. Finally, urban females principally engaged in domestic duties are likelier to report that they are required to be so occupied, the compulsion probably cultural in nature, the less relatively suitable the district is to rice cultivation, with this effect too confined to natives of the district. Taken together, these findings suggest that rice cultivation has played a cultural role in Indian women's workforce participation.
Keywords: Z1; 330; deep roots of culture; female labor force participation; India